2006
DOI: 10.1007/s11558-006-6612-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of IMF programs: A comparison of matching and instrumental-variable estimators

Abstract: IMF programs, program evaluation, sample selection bias,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 22 publications
3
70
1
Order By: Relevance
“…The effect is substantial, accounting for a reduction of 13 See, for example, Dreher (2006), Barro and Lee (2005), Przeworski and Vreeland (2000). See Atoyan and Conway (2006) for a more nuanced view.…”
Section: Resultsmentioning
confidence: 99%
“…The effect is substantial, accounting for a reduction of 13 See, for example, Dreher (2006), Barro and Lee (2005), Przeworski and Vreeland (2000). See Atoyan and Conway (2006) for a more nuanced view.…”
Section: Resultsmentioning
confidence: 99%
“…41 See Goldstein and Montiel (1986) for an extensive treatment. 42 Atoian and Conway (2006) provide a recent application of the method of matching to evaluating the impact of IMF programs.…”
mentioning
confidence: 99%
“…"Recidivism," as they label this phenomenon, is associated with extreme poverty, weak external accounts and high levels of foreign debt. A number of studies have found that countries that have used IMF programs in the past are more likely to use them again, suggesting that recidivism is a real phenomenon (Atoian and Conway, 2006;Jensen, 2004;Pop-Eleches, 2009;Sturm, Berger and de Haan, 2005). 3 This paper proposes an alternative to the prevailing view.…”
Section: Moral Hazard and Adverse Selectionmentioning
confidence: 99%